The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.4319/lo.1999.44.6.1370
|View full text |Cite
|
Sign up to set email alerts
|

Mesozooplankton influences on the microbial food web: Direct and indirect trophic interactions in the oligotrophic open ocean

Abstract: The phytoplankton in warm oligotrophic regions of the open oceans is dominated by Ͻ2-m cells too small for efficient direct consumption by mesozooplankton. However, these primary producers are hypothetically linked to higher trophic levels via the cascading impacts of mesozooplankton grazing on intermediate consumers. To assess the magnitudes of these indirect trophic linkages, grazing experiments, involving different concentration treatments of the mixed mesozooplankton community, were performed during cruise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
154
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(163 citation statements)
references
References 43 publications
6
154
0
3
Order By: Relevance
“…The overall net effect of mesozooplankton feeding on phytoplankton in marine environment is counter-balanced by two opposite effects: direct consumption and indirect cascading (nutrient recycling is not considered here; Calbet and Landry, 1999). The trophic interactions are particularly complex in subtropical coastal and estuarine environments where planktonic abundances, compositions and mesozooplankton feeding preferences are temporally variable because of dynamic hydrographic conditions (Gifford et al, 2007 and this study).…”
Section: Discussion the Net Effect Of Mesozooplankton Feeding On Phytmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall net effect of mesozooplankton feeding on phytoplankton in marine environment is counter-balanced by two opposite effects: direct consumption and indirect cascading (nutrient recycling is not considered here; Calbet and Landry, 1999). The trophic interactions are particularly complex in subtropical coastal and estuarine environments where planktonic abundances, compositions and mesozooplankton feeding preferences are temporally variable because of dynamic hydrographic conditions (Gifford et al, 2007 and this study).…”
Section: Discussion the Net Effect Of Mesozooplankton Feeding On Phytmentioning
confidence: 99%
“…Generally, small-sized phytoplankton (<5 µm) were the preferential food items for microzooplankton, while they were generally too small to be directly ingested by the majority of mesozooplankton species (Calbet and Landry, 1999;Froneman, 2002;Liu and Dagg, 2003;Liu et al, 2005a and this study). A parallel study of our research through HPLC pigment analysis also showed that the clearance rates of mesozooplankton on small-sized phytoplankton, green algae and Synechococcus, were generally negative due to trophic cascades (Liu et al, 2010).…”
Section: The Effect Of Mesozooplankton Size-selective Feedingmentioning
confidence: 99%
“…Regression relationships between mortality coefficients of taxon-specific marker pigments and biovolumes of specific grazer size fractions were less impressive, even when significant. For instance, picoplankton mean mortality, computed as the average rate estimates for DVchl a, α-CAR, chl b and ZEAX, was well correlated with total heterotrophs (p < 0.05), but not significantly related to < 5 µm heterotrophic flagellates (R = 0.29, not shown), their likely dominant consumers in nature (Calbet & Landry 1999). In addition, diatom (FUCO) mortality was significantly correlated with biovolumes of > 20 µm CIL and > 20 µm total heterotrophs (R = 0.38, not shown), but neither relationship explained more than 25% of the variability in the grazing rate estimates.…”
Section: Production and Grazing Relationshipsmentioning
confidence: 99%
“…Given an increase in mortality rates of PRO, we would have expected to find a significant relationship with biovolume of small heterotrophic flagellates (Calbet & Landry 1999). The fact that experimental water and samples for < 20 µm protists were usually taken from different hydrocasts may have confounded any underlying relationships, but there could be other factors as well.…”
Section: Grazing Relationshipsmentioning
confidence: 99%
“…Copepods also both produce Nejstgaard et al Molecular detection fecal pellets that may sediment and are important consumers of sedimenting material (Turner 2002). Copepods may therefore act as key top-down regulators both of the marine plankton food web and of the vertical flux of materials (Verity and Smetacek 1996;Verity 1998;Calbet and Landry 1999;Svensen and Nejstgaard in press). In order to quantify the trophic interactions of copepods and other mesozooplankton in situ, it is not only necessary to assess all important prey, including heterotrophs, but it should also be done with an absolute minimum of handling and temporal and spatial confinement prior to collection and analysis of the predator.…”
mentioning
confidence: 99%